Effects of Prescribed-Fire Timing on Stocker Cattle Performance, Forage Biomass Accumulation, and Native Plant Species Composition - Z. M. Duncan; A. J. Tajchman; J. Lemmon; W. R. Hollenbeck; D. A. Blasi; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this experiment was to document the effects of prescribed-fire timing on stocker cattle performance, forage biomass accumulation, soil cover, and plant species composition in the Kansas Flint Hills. Study Description:A total of 1,416 yearling stocker cattle were assigned to one of three prescribed-burn treatments: spring (April 9 ± 5.1 days), summer (August 23 ± 4.9 days), or fall (September 29 ± 8.7 days) over a 4-year period. Calves were grazed from May to August for 90 days. Individual body weights were recorded at the beginning and end of the grazing season. Native plant composition and soil cover were evaluated annually using a modified step-point method, and forage biomass was measured biannually. The Bottom Line:Flint Hills ranchers can employ late-summer prescribed fires to manage sericea lespedeza (Lespedeza cuneata) infestations without negatively impacting stocker cattle growth performance, forage biomass accumulation, or native rangeland plant species composition.
Keywords: grazing; prescribed fire; sericea lespedeza